2005
DOI: 10.1158/1535-7163.mct-05-0149
|View full text |Cite
|
Sign up to set email alerts
|

The phosphatidylinositol-3-kinase inhibitor PX-866 overcomes resistance to the epidermal growth factor receptor inhibitor gefitinib in A-549 human non–small cell lung cancer xenografts

Abstract: Epidermal growth factor receptor (EGFR) inhibitors such as gefitinib show antitumor activity in a subset of non -small cell lung cancer (NSCLC) patients having mutated EGFR. Recent work shows that phosphatidylinositol-3-kinase (PI3-K) is coupled to the EGFR only in NSCLC cell lines expressing ErbB-3 and that EGFR inhibitors do not inhibit PI3-K signaling in these cells. The central role PI3-K plays in cell survival suggests that a PI3-K inhibitor offers a strategy to increase the antitumor activity of EGFR inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
109
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 143 publications
(111 citation statements)
references
References 51 publications
2
109
0
Order By: Relevance
“…PX866, an inhibitor of the p110α catalytic subunit of PI3K, potentiated the antitumor activity of gefitinib against large A549 xenografts, giving complete tumor growth control in the early stages of treatment. 424 Additive effects of another PI3K inhibitor, LY294002, with gefitinib were also noted in H460 lung cancer cells. 421 These results suggest pathways to PI3K activation in addition to that controlled by EGFR.…”
Section: Erbb3 Egfr Mutation and Clinical Responsiveness To Egfr Inhmentioning
confidence: 97%
“…PX866, an inhibitor of the p110α catalytic subunit of PI3K, potentiated the antitumor activity of gefitinib against large A549 xenografts, giving complete tumor growth control in the early stages of treatment. 424 Additive effects of another PI3K inhibitor, LY294002, with gefitinib were also noted in H460 lung cancer cells. 421 These results suggest pathways to PI3K activation in addition to that controlled by EGFR.…”
Section: Erbb3 Egfr Mutation and Clinical Responsiveness To Egfr Inhmentioning
confidence: 97%
“…In parallel with their preclinical use, the scaffolds of wortmannin and LY294002 have been the subjects of intense lead optimization efforts directed at improving upon the pharmaceutical limitations of the parent compounds. Thus, using wortmannin as a starting point, broad-spectrum PI3K inhibitors with improved pharmaceutical properties and therapeutic indexes such as PWT-458 (compound 3, Figure 2; Yu et al, 2005) and PX-866 (compound 4, Figure 2; Ihle et al, 2005;Howes et al, 2007) have been reported. PWT-458 is a PEGylated derivative of wortmannin that has a higher therapeutic index in preclinical animal models compared to the parent compound.…”
Section: Inhibitors Of the Lipid Kinase Activity Of Pi3kmentioning
confidence: 99%
“…Relatively few in vivo studies have been conducted to demonstrate its efficacy on the inhibition of growth of cancer xenogratfs, but some severe side effects, such as dry and scaly skin, appeared in treated mice. 41 Clearly, the use of nonselective PI3K inhibitors, such as the recently described wortmannin derivative PX-866, 168 is likely to be associated with undesirable side effects (e.g. hyperglycemia) because of the many important physiological targets of this lipid kinase.…”
Section: Non-selective Pi3k Inhibitorsmentioning
confidence: 99%